Actions to reduce maternal and perinatal morbidity and mortality in multiple gestation - Mere del Castillo, Juan (2015)
OBJECTIVE: To know characteristics of multiple pregnancies and to determine benefits of early diagnosis, prenatal control and continuous prenatal assessment to decrease perinatal morbidity and mortality in pregnant women at Loayza Hospital. DESIGN: Descriptive and retrospective study of multiple gestations occurred during 1,997. RESULTS: In 42 multiple pregnancies (39 twins - 3 triplets; incidence: 1: 125 and 1: 1,625) with maternal ages from 17 to 42 years old, 73,8% (31) bad good prenatal controls; 90,5% got ultrasound diagnosis during prenatal control, before 28 weeks in 61,9% (26 patients); 42,9% of pregnancies reached term and the most frequent pathologies were anemia, preeclampsia, disminishing the chance of preterm labor in comparison with previous studies. Abdominal delivery was 76,2% because of an abnormal fetal position (44,8%), severe preeclampsia (20,7%) and previous cesarean section (13,8%). There was no significant difference in Apgar score between first and second twin. Severe bypoxia at I 'was 3,4% of all (1 fetal death). At 5' > 95% bad Apgar score ³ 7. There was no diference between weight of first and second twin either. Neonatal respiratory distress syndrome was 18,4%, sepsis 11,5% and jaundice, 4,6%. The perinatal mortality decreased from 158,22/1,000 newborn alive (1981-1985) to 23,52/1,000 newborn alive (1997). CONCLUSIONS: Early diagnosis, good prenatal control and maternal and fetal surveillance reduce perinatal morbidity and mortality in multiple pregnancies.